The Facies and Metamorphism Types Determination of Metamorphic Rock in The Part of Mekongga Complex - M. Musnajam; Ahmad Tarmidzi Abd Karim; N. Nurfadillah; Fahrudi Ahwan Ikhsan; Andri Estining Sejati (Department of Geography Education, University of Jember, 2020)
Lambolemo Village is geomorphologically dominated by hilly slopes morphology. Lithology in the form of metamorphic rocks are mica schists and chlorite schists. The present research aimed to determine the facies and metamorphism types of metamorphic rocks in Lambolemo Village. The research methods engaged were field observation and laboratory observation utilizing petrographic analysis. Observations stage generated texture data and set of mineral both macroscopically and microscopically. The minerals were discovered within metamorphic rock of the research area, namely: muscovite, quartz, biotite, and chlorite. These findings then classified into two zones, there were chlorite zone and biotite zone. These zones were embodied into greenschist facies with chlorite mineral index. The greenschist facies was characterized with chlorite, albit, epidote, and actinolite minerals appearance. The metamorphic rock had a foliation structure. The structure was commonly generated by a regional metamorphic process, which was particularly a feature of the clear alignment, translucent minerals from flat minerals, such as : mica, chlorite and minerals that obtained fibers or scents. Keywords: Determination; Facies; Metamorfism Type Copyright (c) 2020 Geosfera Indonesia Journal and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License